Contemporary business strategies and models - Ezenwa, Joe (Lagos, Nigeria : Rockfields Nigeria, 2012)
The book presents different business strategies and models which corporate organisations can use to enable them achieve enhanced corporate performance.
Includes bibliographical references.
oif 19/09/14
Loan
Keywords: Strategic management; Business planning; Organisational performance; Business strategies